2008
DOI: 10.1177/000313480807400802
|View full text |Cite
|
Sign up to set email alerts
|

Blood Glucose Variability is Associated with Mortality in the Surgical Intensive Care Unit

Abstract: Intensive insulin therapy has widely and rapidly been adopted as the standard of care for the treatment of hyperglycemia in the intensive care unit (ICU). Variability in blood glucose is increasingly recognized as an important factor in outcomes in the chronic diabetic in addition to hemoglobin A1C. We tested the hypothesis that measures of blood glucose variability would be associated with mortality in the surgical ICU. A retrospective analysis of a cohort of ventilated, critically ill surgical and trauma ICU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(66 citation statements)
references
References 21 publications
6
57
0
3
Order By: Relevance
“…presence of previous diabetes, of a neurological impairment), to the treatment (amount and route of calories provided) and to the time from injury are not well defined. A number of observational studies confirmed a strong association between severe hyperglycemia (>180 mg/dl, 10 mmol/l) [341], marked glycemic variability (coefficient of variation > 20%) [342,343], mild hypoglycemia (<70 mg/dl, 3.9 mmol/l) [344] and increased mortality. However the prospective trials remain inconclusive, owing to differences in practices and to the difficulties in achieving safe and effective glycemic control.…”
Section: Commentary To Recommendations 53 and 54mentioning
confidence: 99%
“…presence of previous diabetes, of a neurological impairment), to the treatment (amount and route of calories provided) and to the time from injury are not well defined. A number of observational studies confirmed a strong association between severe hyperglycemia (>180 mg/dl, 10 mmol/l) [341], marked glycemic variability (coefficient of variation > 20%) [342,343], mild hypoglycemia (<70 mg/dl, 3.9 mmol/l) [344] and increased mortality. However the prospective trials remain inconclusive, owing to differences in practices and to the difficulties in achieving safe and effective glycemic control.…”
Section: Commentary To Recommendations 53 and 54mentioning
confidence: 99%
“…Increased BG variability was associated with an increased risk of death. 123 This finding was confirmed in a 2012 study where the risk of mortality increased with increased BG variability (adjusted relative risk: 1.61; 95% CI: 1.47-1.78). 125 This demonstrates the importance of minimizing BG variability while on IIT.…”
Section: Risks Of Hypoglycemiamentioning
confidence: 72%
“…Several studies have indicated that BG variability is a significant risk factor for mortality and the development of hypoglycemia in the critically ill population. 70,82,[123][124][125] When looking at surgical ICU patients, Kauffman et al 70 found a patient's BG variability increased in the 24 hours that preceded his or her hypoglycemic event. In another study examining critically ill surgical patients receiving IIT, ICU survivors and nonsurvivors had similar mean BG values over time, but the nonsurvivors had significantly more BG variability (P,0.001).…”
Section: Risks Of Hypoglycemiamentioning
confidence: 99%
“…Poor microand macrovascular status has the potential to adversely affect the prognosis of acute stroke. On the other hand, in at least three retrospective studies, the positive association between GV and increased mortality in ICU patients were shown to be more prominent in non-diabetic patients [15,[37][38][39]. In addition, a similar association was also observed in cases with traumatic brain injury [40].…”
Section: Discussionmentioning
confidence: 89%